2011
DOI: 10.1007/s12011-011-9195-6
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Selenium on Hepatic Mitochondrial Respiratory Control Ratio and Respiratory Chain Complex Activities in Ducklings Intoxicated with Aflatoxin B1

Abstract: To investigate the protection of selenium on hepatic mitochondrial functions, 90 7-day-old ducklings were randomly divided into three groups (groups I-III). Group I was used as a blank control. Group II was administered with aflatoxin B(1) (0.1 mg/kg body weight). Group III was administered with aflatoxin B(1) (0.1 mg/kg body weight) plus selenium (sodium selenite, 1 mg/kg body weight). All treatments were given once daily for 21 days. The results showed that the activities of hepatic mitochondrial complexes I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Humans are exposed to these metals from numerous sources, including contaminated air, water, soil, and food. Selenium has been shown to alter heavy metal toxicity specially mercury which cause adverse effects on the various tissue parameters [15,24,31,[47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Humans are exposed to these metals from numerous sources, including contaminated air, water, soil, and food. Selenium has been shown to alter heavy metal toxicity specially mercury which cause adverse effects on the various tissue parameters [15,24,31,[47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of ROS and downregulation of physiological antioxidant has a dual effect of oxidative stress. Aflatoxin B 1 was found to act through this way in ducklings . Molecular pathways of mitochondrial dysfunction and cellular events are shown in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Treatment of 7‐day‐old ducklings with aflatoxin B1, a potent carcinogen produced by HYPERLINK “https://en.wikipedia.org/wiki/Aspergillus_flavus“\o “Aspergillus flavus” Aspergillus flavus and HYPERLINK “https://en.wikipedia.org/wiki/A._parasiticus“\o “A. parasiticus” A. parasiticus (0.1 mg/kg body weight), significantly increased the activity of hepatic mitochondrial complexes I‐IV and induced hepatic mitochondrial respiratory dysfunction . It also decreased the activity of hepatic mitochondrial enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH‐Px), GR, and mitochondrial malondialdehyde (MDA), along with a significant induction of mitochondrial antioxidant dysfunction in ducklings .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ROS caused by aflatoxins are considered to be main mechanisms leading to hepatotoxicity . Recent reports indicated that antioxidant natural components have potential role on AFB1‐induced oxidative toxicity in animal models although their protective results on the toxicity are conflicting …”
Section: Introductionmentioning
confidence: 99%
“…6 Recent reports indicated that antioxidant natural components have potential role on AFB1-induced oxidative toxicity in animal models although their protective results on the toxicity are conflicting. 2,7,8 Liver protectors have often been detected when studying the effect of substances purified from extracts of natural products to which folk medicine has attributed therapeutic properties. Caffeic acid phenethyl ester (CAPE) is a flavonoid-like compound and an active component of propolis from honeybee hives and it has been used in traditional medicine in the Far East for decades.…”
Section: Introductionmentioning
confidence: 99%